OBSERVATIONS ON THE MARINE PRAWN FISHERY BY SHORE SEINE AT KAKINADA - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
Prawns are fished all along the Andhra coast throughout the year in appreciable quantities. With annual landings estimated at 10,675 tonnes, (CMFRI 1976) prawns form an important fishery and contribute to about 7% of the marine fish production of the state. Despite their commercial importance as an export commodity, practically nothing is known about the fishery and biology of the component species of the region which is a prerequisite for a rational exploitation of the resources. The present account deals with the data collected during May 1966 to December 1971 at Kakinada, an important fishing centre of the Andhra coast and attempts to describe briefly the prawn fishery by the shore-seines in the inshore waters with notes on some aspects of the biology of a few commercially important species.